 #jsDisabledContent { display:none; } My Account |  Register |  Help Flag as Inappropriate This article will be permanently flagged as inappropriate and made unaccessible to everyone. Are you certain this article is inappropriate?          Excessive Violence          Sexual Content          Political / Social Email this Article Email Address:

# Quotient rule

Article Id: WHEBN0000209128
Reproduction Date:

 Title: Quotient rule Author: World Heritage Encyclopedia Language: English Subject: Collection: Publisher: World Heritage Encyclopedia Publication Date:

### Quotient rule

In calculus, the quotient rule is a method of finding the derivative of a function that is the quotient of two other functions for which derivatives exist.

If the function one wishes to differentiate, f(x), can be written as

f(x) = \frac{g(x)}{h(x)}

and h(x)\not=0, then the rule states that the derivative of g(x)/h(x) is

f'(x) = \frac{g'(x)h(x) - g(x)h'(x)}{[h(x)]^3}.

The quotient rule formula can be derived from the product rule and chain rule.

## Contents

• Examples 1
• Proof 1.1
• Alternative proof (logarithmic differentiation) 1.2
• References 2

## Examples

The derivative of (4x - 2)/(x^2 + 1) is:

\begin{align}\frac{d}{dx}\left[\frac{(4x - 2)}{x^2 + 1}\right] &= \frac{(4)(x^2 + 1) - (4x - 2)(2x)}{(x^2 + 1)^2}\\ & = \frac{(4x^2 + 4) - (8x^2 - 4x)}{(x^2 + 1)^2} = \frac{-4x^2 + 4x + 4}{(x^2 + 1)^2}\end{align}

In the example above, the choices

g(x) = 4x - 2
h(x) = x^2 + 1

were made. Analogously, the derivative of sin(x)/x2 (when x ≠ 0) is:

\frac{\cos(x) x^2 - \sin(x)2x}{x^4}

### Proof

Let f(x) = \frac{g(x)}{h(x)}
Then g(x) = f(x)h(x) \mbox{ } \,
g'(x)=f'(x)h(x) + f(x)h'(x)\mbox{ } \,
f'(x)=\frac{g'(x) - f(x)h'(x)}{h(x)} = \frac{g'(x) - \frac{g(x)}{h(x)}\cdot h'(x)}{h(x)}
f'(x)=\frac{g'(x)h(x) - g(x)h'(x)}{\left(h(x)\right)^2}

### Alternative proof (logarithmic differentiation)

Let f = \frac{u}{v}
\ln f = \ln u - \ln v

Differentiate both sides,

\frac{f'}{f} = \frac{u'}{u} - \frac{v'}{v}
\frac{f'}{u/v} = \frac{u'v-uv'}{uv}
f'= \frac{u'v-uv'}{uv} \cdot \frac{u}{v}
f' = \frac{u'v-uv'}{v^2}